2021
DOI: 10.1007/s11845-021-02732-x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of olfactory dysfunction with lung involvement and severity of COVID-19

Abstract: Background Olfactory dysfunction (OD) is a significant symptom of COVID-19 and may be the earliest symptom, or it may sometimes be the only manifestation of the disease. Aims To investigate whether OD is correlated with chest computed tomography (CT) findings, blood test parameters, and disease severity in COVID-19 patients. Methods The files of COVID-19 patients were retrospectively reviewed, and the ones who had information about smelling s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 30 publications
2
8
2
Order By: Relevance
“…Regarding more specifically laboratory data, we can observe a tendency of less abnormal results in the OD group compared to the no‐OD group with less lymphopenia ( p = 0.126), longer prothrombin time ( p = 0.126), and higher kidney clearance ( p = 0.154). Other studies have also found a significant relationship between OD and less abnormal laboratory results 9,13,18,34 . Concerning the radiological data, we did not find any significant correlation between OD and thoracic imaging features but a tendency with the high OD group that was associated with less extension >25% (43.1% vs. 59.3%, p = 0.157) on the thoracic CT scan.…”
Section: Discussioncontrasting
confidence: 71%
See 3 more Smart Citations
“…Regarding more specifically laboratory data, we can observe a tendency of less abnormal results in the OD group compared to the no‐OD group with less lymphopenia ( p = 0.126), longer prothrombin time ( p = 0.126), and higher kidney clearance ( p = 0.154). Other studies have also found a significant relationship between OD and less abnormal laboratory results 9,13,18,34 . Concerning the radiological data, we did not find any significant correlation between OD and thoracic imaging features but a tendency with the high OD group that was associated with less extension >25% (43.1% vs. 59.3%, p = 0.157) on the thoracic CT scan.…”
Section: Discussioncontrasting
confidence: 71%
“…Only one study in our review mentioned a significant prevalence of OD in cardiovascular disease. 33 Concerning laboratory data in the first analysis, there was no significant difference between the OD group and the no-OD group but some trends like less lymphopenia (as for some studies: Talavera et al, 9 Yağmur et al, 34 Foster et al, 18 and Izquierdo-Dominguez et al, 13 ), higher clearance CKD (as for Talavera et al, 9 ), longer TP, and an lower level of hemoglobin in the OD group compared with the no-OD group. Interestingly in the second analysis, we did not find the previous trends except for creatinine clearance CKD, high OD being associated with significantly higher clearance CKD (mean 89.0 ± 21.1…”
Section: Population Characteristics: Od Patients Seemed To Have Bette...mentioning
confidence: 84%
See 2 more Smart Citations
“…In contrast, Singer-Cornelius et al suggested, based on a lack of significant associations between the two conditions in objective tests, that GD and OD are two independent symptoms ( 37 ). A negative correlation has been demonstrated between OD and post-admission severity and mortality of COVID-19 in several studies ( 49 , 50 ), in direct contrast to a report on clinical outcomes by Tabari et al ( 51 ). Speth et al showed that in addition to GD, OD severity was significantly associated with depression and anxiety ( 52 ).…”
Section: Clinical Characteristicsmentioning
confidence: 65%